Hydatid cysts of the lung. (7th September 2010) - Widdrington, J D; Echevarria, C; Bone, M; Ellis, R
Abstract : Cystic hydatid disease is a zoonosis caused by infection with the larval cysts of Echinococcus granulosus . Cysts commonly develop in the liver and lungs. Diagnosis in non-endemic regions is often delayed due to a failure to consider hydatidosis. This results from a non-specific presentation and a failure to record an accurate geographical history. The diagnosis requires integrating an appropriate index of suspicion with correct interpretation of imaging and serological tests. In our case, a 44-year-old woman of Yemeni origin presented to a UK hospital with chest pain, pruritus and weight loss. Following detection of pulmonary nodules, a CT-guided biopsy was carried out to exclude malignancy. Iatrogenic cyst rupture precipitated an acute eosinophilic pleurisy. Cystic hydatid disease was subsequently diagnosed following strongly positive hydatid serological tests. This case illustrates the importance of considering diagnoses appropriate to an individual's geographical history particularly in the context of rising immigration and foreign travel.